Implementation of Default Settlement in Pawn Agreements (Study at PT. Awi Gadai Yogyakarta) - Yafi’ Sikka Kandela; Endang Heriyani (Lembaga Teewan Journal Solutions, 2026)
Non-bank financial institutions contribute to the economic development of the community, particularly by serving the economic needs of communities that cannot be reached by banking institutions. PT. Awi Gadai Yogyakarta is a non-bank financial institution that helps the economy of small communities by making it easier to obtain funds through loans secured by pawning. The issues raised are the resolution implemented by PT. Awi Gadai in the event of a customer's default and the legal protection provided to the customer or mortgagor in the event of a default under the pawning agreement at PT. Awi Gadai Yogyakarta. The purpose of this study is to determine the resolution implemented by PT. Awi Gadai in the event of a customer's default and to determine the legal protection provided to the customer or mortgage in the event of a default under the pawning agreement at PT. Awi Gadai. The type of research conducted is normative and empirical legal research. Data collection techniques include literature reviews and interviews with informants. The results indicate that PT. Awi Gadai resolves defaults through auctioning collateral, and the legal protection provided to the customer or mortgagor is through insurance to ensure the existence of the collateral.